Risk factors for scabies in school children: a systematic review - K.J.J.K. Jetly; F.E. Ibrahim; I.K.A. Karim; C. Jeevanathan; Khalid Mokti; Pang, Nicholas Tze Ping; Syed Sharizman Syed Abdul Rahim; Mohammad Saffree Jeffree; Z.I. Azhar; M.R. Hassan; Mohd Faizal Madrim; Abdul Rahman Ramdzan; et al. (Dynasty Publishing House, 2022)
Scabies is one of the most common itchy dermatoses, mainly in vulnerable age groups such as young children and the elderly. Although rarely fatal, it can lead to several severe complications. Its occurrence has been attributed to low-income countries, low socioeconomic levels, lack of knowledge of scabies and preventive health behaviors, overcrowding, and poor sanitation. This review aims to determine the risk factors for scabies in children. Materials and methods. The search was performed in 4 main databases: PubMed, SCOPUS, World of Science (WOS), and Google Scholar. The target population was school children (community/boarding/primary school) that fulfilled the inclusion criteria. The case studies articles, narrative articles, review papers, and articles focusing on general skin outcomes were excluded from this review. Results. A total of 11 studies were included in this review after systematic assessment and appraisal. Scabies infection is significantly higher in children living in urban areas with an adjusted odds ratio (aOR) of 6.9 times compared to rural areas. Scabies occurrence in children is significantly higher in illiterate parents (aOR = 3.49), low annual household income (aOR = 2.13), inaccessibility and poor utilization of water (aOR = 1.64), and large families (family size >4) (aOR = 1.82). School factors that are significant risk factors for scabies include the level of education (aOR = 1.67), number of students per dormitory ≤ 10 (aOR = 6.99), and no access to the school infirmary (aOR = 1.62). Individual factors such as poor personal hygiene (aOR = 1.69) and environmental factors such as high temperature and low humidity (adjusted hazard ratio (aHR) = 2.37) also significantly contribute to scabies infection. Conclusion. Risk factors for scabies are multifactorial, including sociodemographic factors, parent socioeconomic status, housing, family, school, individual and environmental factors. Hence, public health interventions should address all the factors to ensure effective prevention and control of scabies among children.